2018
DOI: 10.1111/micc.12506
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐phosphate protects against brain microvascular endothelial junctional protein disorganization and barrier dysfunction caused by alcohol

Abstract: Objective: Sphingosine-1-phosphate (S1P) has known endothelial barrier protective properties, but whether this extends to the blood-brain barrier (BBB) is unclear. We hypothesized that alcohol-induced disruption of brain microvascular endothelial barrier function and junctional protein organization can be ameliorated by S1P treatment. Methods: Cultured primary human brain microvascular endothelial cell (HBMEC) monolayers were used to characterize endothelial-specific mechanisms of BBB regulation. Transendoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…TER served as an indicator of barrier function of endothelial cell monolayers. TER was determined using an electrical cell‐substrate impedance sensor (ECIS) (Applied Biophysics) as previously described 24,27 . This method allows for real‐time detection of small, momentary changes in barrier function relating to nanometer‐scale changes in junctional structures 37 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TER served as an indicator of barrier function of endothelial cell monolayers. TER was determined using an electrical cell‐substrate impedance sensor (ECIS) (Applied Biophysics) as previously described 24,27 . This method allows for real‐time detection of small, momentary changes in barrier function relating to nanometer‐scale changes in junctional structures 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Endothelial cells have a critical role in controlling blood‐tissue gas and solute exchange 19 . The barrier function of the endothelium depends on the integrity of endothelial structure, which can be actively altered by the responses of endothelial cells to various inflammatory mediators, growth factors, and physical forces 20‐25 . Endothelial junctional proteins and cytoskeleton dynamics have a well‐characterized role in endothelial health 23,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…The direct effect of S1P on cultured BMECs remains controversial. Some research groups have reported barrier enhancement following treatment with S1P ( van Doorn et al, 2012 ; Alves et al, 2019 ), while other research groups found that S1P decreased barrier properties in BMECs ( Wiltshire et al, 2016 ; Nakagawa and Aruga, 2020 ). Given that S1P has different effects on endothelial barrier function depending on the S1PRs involved ( Camm et al, 2014 ), the differences between these conflicting findings may be caused by altered expression of S1PRs in different cell types and culture conditions.…”
Section: Inflammatory Mediators Involved In Bbb Dysfunction and Related Intracellular Signaling Pathways In Bmecsmentioning
confidence: 99%
“…However, more direct approaches could also be more effective. Several investigators have shown with both in vitro and animal models that the bioactive lipid sphingosine-1-phosphate (S1P) can reduce microvascular permeability in a variety of models of inflammation [62][63][64][65][66]. S1P and drugs that activate S1P receptor-1 have been shown to reduce microvascular leakage following experimental trauma in rodents [38,40,67].…”
Section: Microvascular Leakage and The Lymphatic Safety Factormentioning
confidence: 99%
“…Would decreasing permeability of the capillaries and venules reduce or alleviate lymphedema? This remains a significant question considering that specific therapeutics that reduce microvascular permeability by directly targeting blood endothelial cells, such as S1P [38, 40, 64] or sigma receptor agonists [128], remain in an experimental stage. Also, from a therapeutic perspective, there is concern that common agonists/drugs typically affect both vascular and lymphatic endothelia.…”
Section: Introductionmentioning
confidence: 99%